PERAN GURU WALI KELAS DALAM MEMBENTUK SIKAP SOSIAL SISWA SDN OEHENDAK KOTA KUPANG - Koro, Maxsel; Lehan, Andriyani A. D.; Tukan, Fransiskus Bera (Journal of Character and ELementary Education, 2023)
The aim of this research was to investigate how homeroom teachers influence the development of students' social attitudes at SDN Oehendak, Kupang City. The research employed a descriptive qualitative approach was employed, involving data collection methods like observation, interviews, and documentation. Two specific classes, namely, class II and V, were chosen as the focus of the research. The findings of this investigation demonstrate that the observations of the teacher's role in molding students' social attitudes show a positive impact on their overall social development. even more optimally in forming social attitudes both the students themselves and the school environment must support each other in order to create good social attitudes. Then the results of observations of social attitudes can also be supported by several actions given by the teacher to form social attitudes through discussion activities, through reprimands or warnings, advice, and sanctions. Based on the aforementioned data, we can draw the conclusion that homeroom teachers play a significant role in molding the social attitudes of students, leading to reaction of good social attitudes